Risk of Stroke or Transient Ischemic Attack After Atrial Fibrillation Ablation with Oral Anticoagulant Use Guided by ECG Monitoring and Pulse Assessment. (10th March 2014) - RILEY, MICHAEL P.; ZADO, ERICA; HUTCHINSON, MATHEW D.; LIN, DAVID; BALA, RUPA; GARCIA, FERMIN C.; CALLANS, DAVID J.; COOPER, JOSHUA M.; VERDINO, RALPH J.; DIXIT, SANJAY; MARCHLINSKI, FRANCIS E.
Oral Anticoagulant Use After AF Ablation Introduction We sought to gain insight into stroke risk after atrial fibrillation (AF) ablation. Methods and Results We followed 1, 990 patients for >1 year (49 ± 29 months) who underwent AF ablation. Prior to stopping oral anticoagulants (OAC), we performed 3‐week transtelephonic ECG monitoring (TTM) and taught patients heart rate and pulse assessment. Documented AF or inability to do monitoring or assess pulse precluded stopping OAC in CHADS2 ≥1 patients. OAC was stopped in 546/840 (65%) with CHADS2 = 0; 384/796 (48%) with CHADS2 = 1 and 101/354 (40%) with CHADS2 ≥ 2. Sixteen strokes or TIAs occurred (0.2%/patient‐year); 5 in CHADS2 = 0 patients (all off OAC); 5 in CHADS2 = 1 (1 off and 4 on OAC); and 6 in CHADS2 ≥2 (2 off and 4 on OAC). Twelve of 16 patients (75%) with stroke or TIA had documented AF. In patients "off " OAC, stroke rate/year stratified by the CHADS2 score was similar (CHADS2 = 0: 0.28%; CHADS2 = 1: 0.07%; CHADS2 ≥2: 0.50%; P = NS). There was no difference in stroke risk "on" versus "off " OAC in CHADS2 = 1 (0.48% vs. 0.07%) or CHADS2 ≥2 (0.39% vs. 0.50%). Risk of major bleeding per patient year "on" OAC was > "off " OAC (13/1, 138 (1.14%) versus 1/832 (0.1%); P<0.016). Conclusions Post‐AF ablation with OAC guided by TTM and pulse assessment: (1) Overall stroke or TIA rate risk is low and risk is due to recurrent AF and (2) OAC can be stopped in 40% of CHADS2 ≥2 patients with low stroke and hemorrhagic risk.